Mechanical behavior of non-persistent joints with different geometric configurations and roughness in solid rock and concrete material. (27th June 2022) - Meng, Fanzhen; Song, Jie; Wang, Xiaoshan; Yue, Zhufeng; Zhou, Xiong; Wang, Zaiquan
Highlights: Geometric configuration of non-persistent joint significantly affects the shear behavior. Joint geometric configuration has limited influence on residual shear stress. Microcrack propagation is restrained under higher normal stress. Peak shear strength decreases with joint aperture. Shear modulus is rarely influenced by joint roughness and aperture. Abstract: The shear behavior and failure mechanism of non-persistent joints or cracks in rock mass and concrete material are determined by both the rock bridges and the joint geometric configurations. In the present study, the synthetic rock mass (SRM) numerical models are established based on the particle flow code 2D (PFC2D), and numerical direct shear tests are then conducted to investigate the mechanical behavior of non-persistent rock joints. Effects of joint geometric configuration, normal stress, joint roughness, and joint aperture on the shear behavior of non-persistent joints are discussed. Results show that shape of the shear stress curves is greatly influenced by the joint geometric configuration. Besides, specimens with a non-persistent joint in the central have the largest shear modulus, the lowest peak shear strength and the smallest number of microcracks as compared with the other two joint types. The average residual shear stress is not significantly influenced by the joint geometric configuration, but fluctuates more dramatically with the increase in JRC value. For the same joint configuration, the microcrack propagation is restrained under higher normal stress, leading to the decrease of the maximum length of cracks with increasing normal stress. The peak shear strength decreases linearly with the increment of joint aperture under a low normal stress, while it tends to be stable when the joint aperture is larger than 2.0 mm under a high normal stress. The shear modulus of joint specimens is rarely influenced by the JRC values and the joint apertures. The obtained conclusions can provide valuable guidance for the stability analysis and micro-seismic (acoustic emission) monitoring of rock slopes, concrete dams and foundations with embedded non-persistent joints or cracks.